2008
DOI: 10.1080/10826070802603187
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive Determination of Saponins in Radix et Rhizoma Notoginseng by Charged Aerosol Detector Coupled with HPLC

Abstract: With continuous development in analytical instruments over recent years, high performance liquid chromatography (HPLC) with various detectors has become very important tools for routine analysis and quality control of TCMs and botanical medicines. As a new ''mass'' detector, charged aerosol detector (CAD) provides an alternative detection method, which ultraviolet (UV) is unable to achieve for components owning almost no chromophore in its chemical structures with the lower sensitivity. With the purpose of eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…Using an HPLC-CAD system, Bai et al . [42] and Wang et al . [43] simultaneously quantified ginsenosides in P. ginseng and P. notoginseng .…”
Section: Methodsmentioning
confidence: 94%
“…Using an HPLC-CAD system, Bai et al . [42] and Wang et al . [43] simultaneously quantified ginsenosides in P. ginseng and P. notoginseng .…”
Section: Methodsmentioning
confidence: 94%
“…been considered as important chemical markers to reflect the characteristics of the medicinal plants. However, it is difficult to determine saponins by a UV detector, for they mostly subject to no chromophores in their structures and the UV absorption is weak or only has end absorption [13]. To overcome these problems, several trails were performed to apply evaporative light scattering detection (ELSD) and CAD for detection of saponins.…”
Section: Quantitative Determination Of Spicatoside Amentioning
confidence: 99%
“…It has been reported that high performance liquid chromatography coupled with charged aerosol detector (HPLC-CAD) method owned the superiority of good reproducibility and excellent sensitivity for the determination of weak chromophore compounds such as saponins [13]. Thus a method for the quantitative determination of spicatoside A was developed using HPLC-CAD.…”
Section: Introductionmentioning
confidence: 99%
“…Bai et al 183 established an HPLC-CAD method for quantitative analysis of notoginsenoside R1, ginsenosides Rg1, Re, Rb1, Rg2, Rh1, and Rd in 30 batches of P. notoginseng samples. The sensitivity of CAD was higher than that of ELSD or UV.…”
Section: Analytical Advancesmentioning
confidence: 99%